2007
DOI: 10.1104/pp.106.088153
|View full text |Cite
|
Sign up to set email alerts
|

The Gravitropic Response of Poplar Trunks: Key Roles of Prestressed Wood Regulation and the Relative Kinetics of Cambial Growth versus Wood Maturation

Abstract: In tree trunks, the motor of gravitropism involves radial growth and differentiation of reaction wood (Archer, 1986). The first aim of this study was to quantify the kinematics of gravitropic response in young poplar (Populus nigra x Populus deltoides, 'I4551') by measuring the kinematics of curvature fields along trunks. Three phases were identified, including latency, upward curving, and an anticipative autotropic decurving, which has been overlooked in research on trees. The biological and mechanical bases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
102
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(112 citation statements)
references
References 36 publications
10
102
0
Order By: Relevance
“…The model allows the role played by the different components (size described by diameter and height, allometric relations between mass, height and diameter, wood quality and variations within the cross-section) to be studied. The maturation strain asymmetry is clearly the main motor of the reaction, so that the strong assumptions of simple models used in previous studies (Fournier et al, 1994a;Coutand et al, 2007) are justified a posteriori. However, other aspects of growth asymmetry (in ring thickness and wood stiffness), contribute significantly to improve the curving process.…”
Section: Discussionmentioning
confidence: 94%
“…The model allows the role played by the different components (size described by diameter and height, allometric relations between mass, height and diameter, wood quality and variations within the cross-section) to be studied. The maturation strain asymmetry is clearly the main motor of the reaction, so that the strong assumptions of simple models used in previous studies (Fournier et al, 1994a;Coutand et al, 2007) are justified a posteriori. However, other aspects of growth asymmetry (in ring thickness and wood stiffness), contribute significantly to improve the curving process.…”
Section: Discussionmentioning
confidence: 94%
“…Number of replicates were 30 for wheat, 15 for Arabidopsis, and 5 for all the other species. Published data were also reprocessed from similar experiments on Impatiens glandilufera stems by Pfeffer (35) and on poplar trunks (Populus deltoides x nigra cv I4551) by Coutand et al (9). More precisely, two types of experiments were conducted, as explained in SI Appendix, section S2.2 and S2.5: (i) detailed kinematics experiments on two model species (Arabidopsis and wheat), based on time-lapse photography and quantitative analysis of curving-decurving kinematics (SI Appendix, sections S2.2 to S2.4) and (ii) simplified morphometric experiments on all the genotypes, to estimate the bending number (through B l = L gz /L c ) and the (transient) global mode M, defined as the maximum number of places below the apex where the tangent to the central line of the organ is vertical (SI Appendix, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…As for all tropisms, a directional stimulus is sensed (gravity in this case), and the curvature of the organ changes over time until a set-angle and a steady-state shape are reached (2,7,8). The change in shape is achieved by differential elongation for organs undergoing primary growth (e.g., coleoptiles) or by differential differentiation and shrinkage of reaction wood for organs undergoing secondary growth (e.g., tree trunks) (9). Tropisms are complex responses, as unlike other plant movements (e.g., fast movements) (5, 10) the motor activity generated is under continuous biological control (e.g., refs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a recent study on the kinematics of the gravitropic movement of artificially tilted poplars (Coutand et al, 2007) revealed three phases: a latency phase (no curving up of the tilted trunk), a gravitropic phase (curving up) and an autotropic phase (decurving enabling the trunk to become straight and vertical). Within this last phase TW is produced on the opposite side.…”
Section: Introductionmentioning
confidence: 99%